Band Spotlight: Phase II Pan Groove - Unknown (Pan Evolution)
This article gives some history on the formation of Phase II Pan Groove. One of the hallmark of Phase II is that from 1974 to the present, the band has played selections by arranger, composer and musical director Len "Boogsie" Sharpe. A list of the names of these selections are included. Phase II became the first steelband in the history of Panorama to win the coveted title of "Panorama Champions" with its 'own tune'.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Arrangers (Musicians) -- Trinidad and Tobago; Sharpe, Len